Decolonising the COVID-19 pandemic: On being in this together - Duncan, Rebecca (Approaching religion, 2021)
At its inception, the COVID-19 pandemic was described as something inherently new, capable of crossing and erasing the economic, racial, gendered, and religious divides that stratify societies around the world. However, the ongoing pandemic is not new or egalitarian, but fuelled by, and fuelling, crises already under way on a global scale. In this article we examine on the one hand the relationship between the pandemic and still-active formations of racialised and gendered power, and on the other the pandemic's inextricability from a dispersed and uneven planetary emergency. As the environmental historian Jason W. Moore notes, this emergency disproportionately affects ‘women, people of colour and (neo)colonial populations’ (2019: 54), and the effects of COVID-19 are similarly unevenly allocated.